Birds of Siberian-pine (Pinus sibirica) forests of the south-east part of Western Siberia (Tomsk Region). Issue 5 (3rd September 2017) - Kuranov, Boris D.; Nekhoroshev, Oleg G.; Mitchell, Peter J.; Milovidov, Sergey P.
Abstract: The article examines the fauna and bird population of Siberian-pine forests in Tomsk Region (the south-east part of Western Siberia) in the summer period. The article is based on data collected by the authors over many years in 12 areas of Siberian-pine forests in various forest subzones. The taxonomical structure of avifauna, the landscape and ecological structure, and species distribution are examined. A comparison has been made of species diversity and population density for birds of sub-taiga Siberian-pine forests in the southern and middle taiga. The authors have identified the leading species of birds in terms of population density in various forest subzones. A tendency towards latitudinal changes in species diversity and population density in Siberian-pine forests has been discovered. The authors have identified the species of birds whose diet includes the nuts of Siberian pines. Data on the bird species of Siberian-pine forests listed in the Red Data Book of Tomsk Region have been included.